2016
DOI: 10.1002/ange.201602441
|View full text |Cite
|
Sign up to set email alerts
|

First Step Towards a Devil's Staircase in Spin‐Crossover Materials

Abstract: The unprecedented bimetallic 2D coordination polymer {Fe[(Hg(SCN)3)2](4,4′‐bipy)2}n exhibits a thermal high‐spin (HS)↔low‐spin (LS) staircase‐like conversion characterized by a multi‐step dependence of the HS molar fraction γHS. Between the fully HS (γHS=1) and LS (γHS=0) phases, two steps associated with different ordering appear in terms of spin‐state concentration waves (SSCW). On the γHS≈0.5 step, a periodic SSCW forms with a HS‐LS‐HS‐LS sequence. On the γHS≈0.34 step, the 4D superspace crystallography str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…The last points concern (iii) incomplete transitions and (iv) two-step or multi-step transitions [76][77][78][79][80][81][82] . The latter, take place with the emergence of ordered intermediate phases, which are stabilized leading to the appearance of one or several plateaus in the thermal-dependence of the order parameters, as reported in several experimental studies, [83][84][85][86] which demonstrated the existence of self-organization of the spin states in these regions. The spatial organizations of the spin states were found under the form of antiferro-like (checkerboard) structure 87,88 or may have more complex structures, like ordered alternate HS and LS sheets as in [Fe(2-pic)3]Cl2.EtOH (pic=2-picolylamine) 83 or modulated HS-LS patterns, where the modulation can be commensurate or incommensurate with the lattice parameter 84,85,86 as obtained re multiple transitions are observed during the thermal transition.…”
Section: Introductionsupporting
confidence: 54%
“…The last points concern (iii) incomplete transitions and (iv) two-step or multi-step transitions [76][77][78][79][80][81][82] . The latter, take place with the emergence of ordered intermediate phases, which are stabilized leading to the appearance of one or several plateaus in the thermal-dependence of the order parameters, as reported in several experimental studies, [83][84][85][86] which demonstrated the existence of self-organization of the spin states in these regions. The spatial organizations of the spin states were found under the form of antiferro-like (checkerboard) structure 87,88 or may have more complex structures, like ordered alternate HS and LS sheets as in [Fe(2-pic)3]Cl2.EtOH (pic=2-picolylamine) 83 or modulated HS-LS patterns, where the modulation can be commensurate or incommensurate with the lattice parameter 84,85,86 as obtained re multiple transitions are observed during the thermal transition.…”
Section: Introductionsupporting
confidence: 54%
“…In addition, these dinuclear species in turn act as linkers between linear [Fe(μ-L)] n 2n+ chains, thus resulting in highly crystalline 2D sheetlike coordination polymers generically formulated as {Fe[μ-(Hg(SeCN) 3 ) 2 ](μ-L) 2 }. Both compounds are isostructural with those obtained from the homologous [Hg(SCN) 4 ] 2− precursor when equivalent L bis-monodentate ligands are used, including 4,4′-bipy 24,25 and tvp. 26 On the basis of the limited number of examples reported so far, this in situ transformation from [Hg(XCN) 4 ] 2− to {[Hg II (XCN) 3 ] 2 (μ-L)} 2− (X = S, Se) seems to be much less favored for X = Se.…”
Section: ■ Resultsmentioning
confidence: 95%
“…Furthermore, the equilibrium temperature for 1, T 1/2 = 170 K, is 55 K higher than the average T 1/2 value shown by its X = S homologue. 24,25 This suggests that the increase in ligand field strength around the Fe II induced by the XCN − (X = S, Se) group does not depend substantially on whether it belongs to the dimeric bridging unit {[Hg II (XCN) 3 ] 2 (μ-L)} 2− or acts as a simple coordinating terminal anion. It is worth noting that differences of similar magnitude in T 1/2 have been found for monomeric 35−44 and polymeric 1D 45−47 and 2D 48−51 [Fe-(L) 2 (NCX) 2 ] SCO complexes.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations